Applications of 129Xe and PFG NMR techniques on adsorption and diffusion of molecular sieve materials - Shushu Gao; Jiamin Yuan; Fangxiu Ye; Zhiqiang Liu; Anming Zheng; Shutao Xu (Journal of Magnetic Resonance Open)
Molecular sieves possess unique properties and have emerged as the predominant catalysts with shape selectivity in the petrochemical industry because of their well-defined pore architectures. However, the existence of a constrained pore surroundings of molecular sieves can limit intracrystalline diffusion, leading to underutilization of the active volume of the molecular sieve or rapid catalysts deactivation during catalytic processes. Moreover, the mechanism of adsorption and diffusion of molecules inside molecular sieves is crucial for the optimization and advancement of catalysts in heterogeneous catalysis. Due to the complexity of the diffusion process in molecular sieve materials, it is very necessary to develop characterization methods that are more sensitive and informative for studying the adsorption and diffusion of guests inside pores. Advancements in characterization techniques and theoretical calculations have led to a more profound comprehension of the adsorption and diffusion properties of molecular sieves at the microscopic scale. This article mainly summarizes the research progress of molecular adsorption and diffusion in molecular sieve materials using advanced 129Xe NMR, hyperpolarized (HP) 129Xe NMR, and pulsed-field gradient (PFG) NMR techniques in recent years and focuses on the principles of these techniques and applicability of the relationship of adsorption-diffusion using these techniques within several molecular sieve systems. Moreover, the effects of the topology and pore connectivity of molecular sieves on the adsorption and diffusion of guest molecules as well as the effects of intracrystalline diffusion on catalytic reactions are discussed.